Comparative analysis of the role of mast cells in murine asthma models using Kit‐sufficient mast cell‐deficient animals. Issue 7 (9th March 2021) - Pohlmeier, Lea; Sonar, Sanchaita Sriwal; Rodewald, Hans‐Reimer; Kopf, Manfred; Tortola, Luigi
Abstract: Background: Asthma is a frequent chronic disease that can potentially severely affect the respiratory capacity and well‐being of patients. Mast cells (MCs) are regarded as major players in human asthma due to their capacity to release crucial inflammatory mediators following allergen exposure. However, unambiguous characterization of their role in animal models has long been hindered by the unavailability of specific MC‐deficient models lacking confounding MC‐unrelated effects. This study aims to examine the role of MCs in Kit ‐sufficient MC‐deficient Cpa3 Cre /+ mice. Methods: We used a variety of models of acute and chronic asthma employing distinct routes and regimes of sensitization. These sensitizations were done via the peritoneal cavity, the skin, or the lung. Additionally, different allergens, i.e. ovalbumin and house dust mite extract, were used. Results: Our results show that the absence of MCs had no impact on the severity of allergic airway inflammation in any of the tested mouse models, as measured by leukocyte infiltration in the airways, cytokine expression, antibody production, airway hyper‐responsiveness and mucus production. Conclusion: This indicates that MCs do not play a major role in murine allergic airway inflammation. Abstract : Mast cell‐deficient mice show similar levels of eosinophilia, neutrophilia, and lymphocyte infiltration compared to wild‐type littermates in several murine models of acute and chronic asthma. The lack of mast cells does not alter cytokine production, IgE, or IgG1 levels in any model. Airway hyper‐responsiveness or goblet cell hyperplasia is unaffected by the absence of mast cells in all models. Abbreviations: Cpa3, carboxypeptidase A3; HDM, house dust mite; Ig, immunoglobulin; OVA, ovalbumin.